Methodology, clinical applications, and future directions of body composition analysis using computed tomography (CT) images: A review. Issue 145 (December 2021) - Tolonen, Antti; Pakarinen, Tomppa; Sassi, Antti; Kyttä, Jere; Cancino, William; Rinta-Kiikka, Irina; Pertuz, Said; Arponen, Otso
Highlights: Sarcopenia is associated with poor prognosis in many diseases and cancers. It is important to diagnose muscle wasting conditions to ensure optimal care. Computed tomography enables accurate body composition analysis. Computed tomography shows great potential for clinical implementation. Abstract: Purpose of the review: We aim to review the methods, current research evidence, and future directions in body composition analysis (BCA) with CT imaging. Recent findings: CT images can be used to evaluate muscle tissue, visceral adipose tissue (VAT), and subcutaneous adipose tissue (SAT) compartments. Manual and semiautomatic segmentation methods are still the gold standards. The segmentation of skeletal muscle tissue and VAT and SAT compartments is most often performed at the level of the 3rd lumbar vertebra. A decreased amount of CT-determined skeletal muscle mass is a marker of impaired survival in many patient populations, including patients with most types of cancer, some surgical patients, and those admitted to the intensive care unit (ICU). Patients with increased VAT are more susceptible to impaired survival / worse outcomes; however, those patients who are critically ill or admitted to the ICU or who will undergo surgery appear to be exceptions. The independent significance of SAT is less well established. Recently, the roles of the CT-determined decrease of muscle mass and increased VAT area and epicardial adipose tissue (EAT) volume have been shown to predict a more debilitating course of illness in patients suffering from severe acute respiratory syndrome coronavirus 2 (COVID-19) infection. Summary: The field of CT-based body composition analysis is rapidly evolving and shows great potential for clinical implementation.